An experimental case study on the effect of condenser geometry in a refrigerator: Sub-cooling and coefficient of performance issues - Borikar, Sanjaykumar A.; Borikar, Dilipkumar A.; Panchal, Hitesh; Cuce, Erdem; Dalkilic, Ahmet Selim; Alrubaie, Ali Jawad; Jaber, Mustafa Musa (ELSEVIER SCI LTD, 2023)
The study aims to establish the role of the condenser and condenser geometry in the performance enhancement of the future generation of mid-sized refrigerators. Experimental and statistical methods were used to examine the influence and significance of ambient temperature, condenser geometry, and heat load on refrigerator per-formance. Experimentation was conducted on the experimental facility under standard designated operating conditions (i.e., 32 degrees C ambient temperature and 5 degrees C fresh food temperature). The experimental evaluations of refrigerators represent increase 13% - 29% in the coefficient of performance and 24% in the sub-cooling for improved factor fixation during the experiment. The analysis of variance comments upon the most influencing input factor that affects the performance most. Experimentally and analytically the combination of ambient temperature and the condenser geometry produces an impact on coefficient of performance and sub-cooling than other combinations. The analysis of variance determined the correct fit of the second-order quadratic model with a root mean square value of 0.994 and a root mean square value adjusted of 0.954.
Keywords: Condenser geometry; Coefficient of performance; Sub-cooling; Analysis of variance; Factorial design; Thermodynamics; Engineering